2019
DOI: 10.3382/ps/pey516
|View full text |Cite
|
Sign up to set email alerts
|

Loop-mediated isothermal amplification: rapid molecular detection of virulence genes associated with avian pathogenic Escherichia coliin poultry

Abstract: Infections with pathogenic Escherichia coli can lead to different animal- and human-associated diseases. E. coli infections are common in intensive poultry farming, and important economic losses can be expected during infections with avian pathogenic E. coli (APEC) strains followed by colibacillosis. Loop-mediated isothermal amplification (LAMP) assays were developed for rapid detection of 3 APEC-associated virulence genes: sitA, traT, and ompT. All 3 LAMP assays are shown to be specific, repeatable, and repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Previously, Obeng et al [ 58 ] and Stromberg et al [ 49 ] recorded the prevalence of APEC in fecal samples from layers and broilers as 10% and 13%. Kogovšek et al [ 59 ] revealed an association of APEC virulence genes with air samples. This evidence shows that the APEC strains harbored by commercial chickens and their environment can be transmitted from bird to bird and farm to farm through a variety of ways, including air, feces and utensils used in farms.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Obeng et al [ 58 ] and Stromberg et al [ 49 ] recorded the prevalence of APEC in fecal samples from layers and broilers as 10% and 13%. Kogovšek et al [ 59 ] revealed an association of APEC virulence genes with air samples. This evidence shows that the APEC strains harbored by commercial chickens and their environment can be transmitted from bird to bird and farm to farm through a variety of ways, including air, feces and utensils used in farms.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the age, resistance, pathogenicity and infection routes of infected chickens, Chicken Colibacillosis include many clinical signs and different disease types. There is a high incidence of diseases in chicken farming, which is responsible for high economic losses in the chicken industry [ 1 , 2 ]. Chicken colibacillosis is clinically characterized by a variety of disease types, including pericarditis, perihepatitis, peritonitis, air sac inflammation and septicemia [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…While Eftekharian et al (2016), detected iutA gene in 70% and lopez banda et al (2014) in 50% of E. coli isolates. The virulence gene (traT) detected in 60% of isolates which nearly to Bok et al (2020) 54.9% while 88.8%and 88.1% detected by Marwa Hassaen et al (2020) and Kogovšek et al (2019). While, 47.7% detected by Ferreira et al (2018).…”
Section: Discussionmentioning
confidence: 90%